Dietary Dunaliella salina microalgae enriches eggs with carotenoids and long-chain omega-3 fatty acids, enhancing the antioxidant and immune responses in heat-stressed laying hens - Madkour, Mahmoud; Ali, Sami I.; Alagawany, Mahmoud; El-Kholy, Mohamed S.; El-Baz, Farouk K.; Alqhtani, Abdulmohsen H.; Alharthi, Abdulrahman S.; Pokoo-Aikins, Anthony; Elolimy, Ahmed A. (Frontiers in Veterinary Science, 2025)
IntroductionDunaliella salina (DS) is a prospective source of bioactive carotenoids, including beta-carotene, zeaxanthin, and omega-3 fatty acids. The effect of dietary supplementation of DS on the productive performance, immune response, and egg quality of heat-stressed laying hens has not been comprehensively studied. We investigated how dietary D. salina supplementation affects the deposition of bioactive carotenoids and omega-3 fatty acids in egg yolks of laying hens experiencing summer heat stress, as determined by the Temperature-Humidity Index (THI). The influence of D. salina supplementation on the productive performance, immune response, and antioxidant status of heat-stressed laying hens was assessed.MethodsA total of 120 Elma-Brown laying hens were assigned to four dietary treatments with DS supplementation at 0 (control), 0.5, 1, and 1.5 g/kg of diet. The experiment lasted 60 days, during which eggs were collected at three time points: 15, 30, and 60 days from the start of the study.Results and discussionincluding DS at 1 g/kg improved egg production and feed conversion, with improved antioxidant status via a marked inhibitory effect on malondialdehyde in heat-stressed laying hens. Dietary 0.5 g/kg DS improved the immune response of heat-stressed laying hens compared to that of the control group. The highest dose of DS (1.5 g/kg diet) increased astaxanthin, zeaxanthin, lutein, and total carotenoids by 9.8%, 50.44%, 49.19%, and 84.21% (p < 0.05), respectively, and decreased β-carotene by 38.61% (p < 0.05), when compared with the control. Feeding DS to heat-stressed laying hens increased the concentrations of the long-chain Omega-3 (docosahexaenoic acid) in egg yolks; the dose of 0.5 g/kg diet for 15 d produced an increase in the DHA content by104.76% above the control group (p < 0.5). Feeding DS improved the nutritional indices of egg yolks, as egg yolks retained a high ratio of monounsaturated fatty acids (MUFA)/polyunsaturated fatty acids (PUFA)/saturated fatty acids, low thrombogenicity index (IT), low atherogenicity index (IA), and high hypocholesterolemic/hypercholesterolemic index (h/H). Feeding heat-stressed laying hens DS improved their productivity and antioxidant status, resulting in functional eggs enriched with bioactive carotenoids (astaxanthin, zeaxanthin, and lutein) and beneficial omega-3 fatty acids.